Alkynone β-trifluoroborates: a new class of amine-specific biocompatible click reagents - Teng, Shenghan (2023)
Amine-targeting reactions that work under biocompatible conditions or in water are green processes that are extremely useful for the synthesis of functional materials and biotherapeutics. Unfortunately, despite the usefulness of this reaction, there are very few good amine-specific click methods reported thus far. Here, we report an amine-specific click reagent using alkynone β-trifluoroborates as the electrophiles. These boron-containing alkynyl reagents exhibit extremely high chemoselectivity toward amines even in the presence of thiols. The resulting oxaboracycle products are bench-stable, displaying the reactivities of both organoborates and enaminones. Intrinsic advantages of this methodology include benign reaction conditions, operational simplicity, remarkable product stability, and excellent chemoselectivity, which satisfy the criteria of click chemistry and demonstrate the high potential in bioconjugation. Hence, this water-based chemical approach is also applicable to the modification of native amino acids, peptides, and proteins. Ultimately, the essential role of water during the reaction was elucidated.